O ensino da educação financeira em uma escola de comunidade Ribeirinha amazônica, por meio de um projeto de extensão - FELIPE, Samara Trindade de Moura (Universidade Federal do Pará, 2024)
Financial Education, a global concerning, seeks to promote financial knowledge. In Brazil, the National Financial Education Strategy (ENEF), created in 2010, has as its main objective promoting Financial Education, including it in the Basic Education curriculum, being treated as a transversal theme that must be addressed in different school subjects. However, not all students have the same financial or cultural reality, and it is essential that this teaching can be adapted to ensure meaningful learning. At the same time, when analyzing the schooling formation of Higher Education students who, in some way, are related to the theme, especially the Mathematics Degree, it is common for topics related to finance to be worked on only the technical repertoire of Financial Mathematics, its mathematical concepts and properties, leaving aside the relation of these notions with public policies and the association between consumption and planning, initial concepts that are essential for a schooling formation in Financial Education that can then be “translated” in future moments in the Basic Education classroom. Given the context, the research on screen starts from the following question